Advancing Long-Term Outdoor Air Pollution Exposure Assessment for Health Studies: Lessons from a Multinational Research Initiative - Hanna Boogaard; Dan L. Crouse; Allison P. Patton; Ellen Mantus; Susanne Breitner-Busch; Jaime E. Hart; Anna Oudin; Shu Yang; Jeffrey D. Yanosky; John Volckens; Jana B. Milford (Current Environmental Health Reports, 2026)

Species Identification of Caviar Using ONT Sequencing—A Case Study - Frederic D. B. Schedel; Nadera Hanifi; Luca Jelacic; Thomas Hankeln; Cornelia Vocke; Ulrich Busch; Ingrid Huber (Fishes, 2026)
The high commercial value and the increasing demand for caviar make it susceptible to illegal trade and fraudulent activities, while mislabelling can occur both deliberately and unintentionally. Therefore, reliable methods are urgently needed to distinguish even closely related sturgeon species for the authentication of declared species in caviar products. In this study, we explore the effectiveness of ONT sequencing combined with nanopore adaptive sampling (NAS) to recover mitochondrial genomes from genomic DNA extracted from two caviar samples. NAS yielded similar percentages of mitochondrial reads as sequencing experiments without using the NAS option. However, NAS substantially increased the percentage of bases that could be mapped against a mitochondrial reference genome, demonstrating its effectiveness in enriching ONT sequencing data for mitochondrial sequences. The percentage of mapped mitochondrial reads varied between two samples in our sequencing experiments, ranging between 2.37% and 10.46%, which is exceptionally high compared to previous studies focusing on the recovery of mitochondrial genomes from genomic DNA. This increase may be attributed to the extraction of genomic DNA from individual fish eggs. To determine the taxonomic identities of the two caviar samples, a phylogenetic analysis was performed that included all available acipenseriform mitochondrial genomes from GenBank, as well as the newly recovered mitochondrial genomes. During this process, four problematic mitochondrial genomes obtained from GenBank were identified, which were characterized by either suggestively low sequence quality, chimeric sequence information, or potential misidentification. This underscores the need for reviewing sequencing data before database submission to avoid negative impacts on research and DNA-based species authentication.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Unveiling the Complex problem with Mdivi-1 - Nico Marx; Nadine Ritter; Paul Disse; Guiscard Seebohm; Karin B. Busch (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Evaluation of DNA lesions and radicals generated by a 233 nm far-UVC LED in superficial ex vivo skin wounds - Loris Busch; Marius Kröger; Johannes Schleusener; Anna Lena Klein; Silke B. Lohan; Martin Guttmann; Cornelia M. Keck; Martina C. Meinke (Journal of Photochemistry and Photobiology B: Biology, 2023)

Urinary concentration of phthalates and bisphenol A during minipuberty is associated with reproductive hormone concentrations in infant boys - Matilde Lærkeholm Müller; Alexander Siegfried Busch; Marie Lindhardt Ljubicic; Emmie N. Upners; Margit B. Fischer; Casper P. Hagen; Jakob Albrethsen; Hanne Frederiksen; Anders Juul; Anna-Maria Andersson (International Journal of Hygiene and Environmental Health, 2023)

Inner mitochondrial membrane structure and fusion dynamics are altered in senescent human iPSC-derived and primary rat cardiomyocytes - Silke Morris; Isidora Molina-Riquelme; Gonzalo Barrientos; Francisco Bravo; Geraldine Aedo; Wileidy Gómez; Daniel Lagos; Hugo Verdejo; Stefan Peischard; Guiscard Seebohm; Olympia Ekaterini Psathaki; Verónica Eisner; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Mobilität einzelner Membranproteine in Mitochondrien - Karin B. Busch (BIOspektrum, 2022)
Mitochondria are enveloped by an outer membrane (OM) and possess a highly complex inner membrane (IM) with multiple cristae invaginations. We asked how the dynamics of the receptor Tom20 in the OM and ATP synthase in the IM would be affected by the membrane architecture. Single molecule tracking of fluorescence-labeled single particles revealed striking differences in the mobility patterns and diffusion coefficients: ATP synthase is trapped in cristae, while Tom20 is highly diffusive.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Wavelength, dose, skin type and skin model related radical formation in skin - M. C. Meinke; L. Busch; S. B. Lohan (Biophysical Reviews, 2021)
The exposure to sun radiation is indispensable to our health; however, a long-term and high exposure could lead to cell damage, erythema, premature skin aging, and promotion of skin tumors. An underlying pathomechanism is the formation of free radicals which may induce oxidative stress at elevated concentrations. Different skin models, such as porcine-, murine-, human- ex vivo skin, reconstructed human skin (RHS) and human skin in vivo, were investigated during and after irradiation using X- and L-band EPR spectroscopy within different spectral regions (UVC to NIR). The amount of radical formation was quantified with the spin probe PCA and the radical types were measured ex vivo with the spin trap DMPO. The radiation dose influences the types of radicals formed in the skin. While reactive oxygen species (ROS) are always pronounced at low doses, there is an increase in lipid oxygen species (LOS) at high doses. Furthermore, the radical types arise independent from the irradiation wavelength, whereas the general amount of radical formation differs with the irradiation wavelength. Heat pre-stressed porcine skin already starts with higher LOS values. Thus, the radical type ratio might be an indicator of stress and the reversal of ROS/LOS constitutes the point where positive stress turns into negative stress.Compared to light skin types, darker types produce less radicals in the ultraviolet, similar amounts in the visible and higher ones in the infrared spectral region, rendering skin type-specific sun protection a necessity.

Lower Vibrio spp. abundances in Zostera marina leaf canopies suggest a novel ecosystem function for temperate seagrass beds - Thorsten B. H. Reusch; Philipp R. Schubert; Silke-Mareike Marten; Diana Gill; Rolf Karez; Kathrin Busch; Ute Hentschel (Marine Biology, 2021)
Seagrasses, a polyphyletic group of about 60 marine angiosperm species, are the foundation of diverse and functionally important marine habitats along sheltered sedimentary coasts. As a novel ecological function with high societal relevance, a role of the seagrass leaf canopy for reducing potentially harmful bacteria has recently been hypothesized in tropical regions, but data for temperate regions are lacking. Here, we tested whether or not the abundance of general bacteria and more specifically, those belonging to the genus Vibrio were reduced within temperate Zostera marina (eelgrass) meadows compared to adjacent sand flats and sampled 5 sites in the south-western Baltic Sea using SCUBA. Compared to non-vegetated area, we found an average reduction of 39% for all Vibrio and 63% for the potentially harmful V. vulnificus/cholerae subtype based on robust plate counting data on Vibrio selective agar. The underlying mechanism of the reduction in bacterial load is currently elusive and clearly merits further study. Our results underline the critical importance of seagrasses in maintaining shallow water ecosystem functioning including water quality and provide further motivation for their protection and restoration.

Ocean and coastal indicators: understanding and coping with climate change at the land-sea interface - Patricia M. Clay; Jennifer Howard; D. Shallin Busch; Lisa L. Colburn; Amber Himes-Cornell; Steven S. Rumrill; Stephani G. Zador; Roger B. Griffis (Climatic Change, 2020)

Critical review: incorporating the arrangement of mitochondria and chloroplasts into models of photosynthesis and carbon isotope discrimination - Nerea Ubierna; Lucas A. Cernusak; Meisha Holloway-Phillips; Florian A. Busch; Asaph B. Cousins; Graham D. Farquhar (Photosynthesis Research, 2019)

The accessory magnocellular neurosecretory system of the rostral human hypothalamus - Morten Møller; Johannes R. Busch; Christina Jacobsen; Sissel B. Lundemose; Niels Lynnerup; Martin F. Rath; Jytte Banner (Cell and Tissue Research, 2018)

Dynamic imaging of mitochondrial membrane proteins in specific sub-organelle membrane locations - Timo Appelhans; Karin B. Busch (Biophysical Reviews, 2017)

The association of children’s mathematic abilities with both adults’ cognitive abilities and intrinsic fronto-parietal networks is altered in preterm-born individuals - J. G. Bäuml; C. Meng; M. Daamen; N. Baumann; B. Busch; P. Bartmann; D. Wolke; H. Boecker; A. Wohlschläger; C. Sorg; Julia Jaekel (Brain Structure and Function, 2017)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2016)

Evaluating markers of epithelial-mesenchymal transition to identify cancer patients at risk for metastatic disease - Evan L. Busch; Temitope O. Keku; David B. Richardson; Stephanie M. Cohen; David A. Eberhard; Christy L. Avery; Robert S. Sandler (Clinical & Experimental Metastasis, 2016)

Atlantic salmon, S almo salar L . are broadly susceptible to isolates representing the N orth A merican genogroups of infectious hematopoietic necrosis virus - G Kurath; J R Winton; O B Dale; M K Purcell; K Falk; R A Busch (Journal of Fish Diseases, 2016)
Beginning in 1992, three epidemic waves of infectious hematopoietic necrosis, often with high mortality, occurred in farmed A tlantic salmon S almo salar L . on the west coast of N orth A merica. We compared the virulence of eleven strains of infectious hematopoietic necrosis virus ( IHNV ), representing the U , M and L genogroups, in experimental challenges of juvenile A tlantic salmon in freshwater. All strains caused mortality and there was wide variation within genogroups: cumulative mortality for five U ‐group strains ranged from 20 to 100%, four M ‐group strains ranged 30‐63% and two L ‐group strains varied from 41 to 81%. Thus, unlike P acific salmonids, there was no apparent correlation of virulence in a particular host species with virus genogroup. The mortality patterns indicated two different phenotypes in terms of kinetics of disease progression and final per cent mortality, with nine strains having moderate virulence and two strains (from the U and L genogroups) having high virulence. These phenotypes were investigated by histopathology and immunohistochemistry to describe the variation in the course of IHNV disease in A tlantic salmon. The results from this study demonstrate that IHNV may become a major threat to farmed A tlantic salmon in other regions of the world where the virus has been, or may be, introduced.

Flicker-Induced Time Dilation Does Not Modulate EEG Correlates of Temporal Encoding - Sophie K. Herbst; Maximilien Chaumon; Trevor B. Penney; Niko A. Busch (Brain Topography, 2015)

Narrow species concepts in the Frullania dilatata–appalachiana–eboracensis complex (Porellales, Jungermanniopsida): evidence from nuclear and chloroplast DNA markers - A. Bombosch; A. Wieneke; A. Busch; R. Jonas; J. Hentschel; H.-P. Kreier; B. Shaw; A. J. Shaw; J. Heinrichs (Plant Systematics and Evolution, 2010)

“Technically Unavoidable” in Terms of Genetically Modified Organisms – an Approach for Food Control - H.-U. Waiblinger; N. Graf; D. Mäde; K. Woll; U. Busch; B. Holland; H. Pilsl; G. Naeumann; R. Reiting; B. Ehrentreich; M. Schulze; B. Tschirdewahn; et al. (Journal of Consumer Protection and Food Safety, 2007)

Epidemiology of rubella infections in Austria: important lessons to be learned - B. Falkensammer; G. Walder; D. Busch; A. Gieauf; M. Dierich; R. Wrzner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Granulocyte colony-stimulating factor (G-CSF) reduces not only gram-negative but also gram-positive infection-associated proinflammatory cytokine release by interaction between Kupffer cells and leukocytes - G. A. Wanner; C. J. Busch; B. Vollmar; M. D. Menger (Inflammation Research, 2004)

Use of the firefly luciferase gene in a barley ( Hordeum vulgare ) transformation system - W. Harwood; S. Ross; S. Bulley; S. Travella; B. Busch; J. Harden; J. Snape (Plant Cell Reports, 2002)

Interaction between electron transport at the plasma membrane and nitrate uptake by maize (Zea mays L.) roots - D. Steffen; O. Dring; M. A. Busch; M. Bttger; S. Lthje (Protoplasma, 2001)

Effect of urea and osmotic cell shrinkage on Ca2+ entry and contraction of vascular smooth muscle cells - C.A. Wagner; S.M. Huber; S. Wärntges; G. Zempel; N.K. Kaba; R. Fux; N. Orth; G.L. Busch; S. Waldegger; I. Lambert; B. Nilius; H. Heinle; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

KATP channel blocker HMR 1883 reduces monophasic action potential shortening during coronary ischemia in anesthetised pigs - K.J. Wirth; J. Uhde; B. Rosenstein; H.C. Englert; H. Gögelein; B.A. Schölkens; A.E. Busch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Degradation of desferrioxamines by Azospirillum irakense: Assignment of metabolites by HPLC/electrospray mass spectrometry - G. Winkelmann; B. Busch; A. Hartmann; G. Kirchhof; R. Süßmuth; G. Jung (BioMetals, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Structural rearrangement in chromosome 2M of Aegilops comosa has prevented the utilization of the Compair and related wheat-Ae. comosa translocations in wheat improvement - S. Nasuda; B. Friebe; W. Busch; R. G. Kynast; B. S. Gill (Theoretical and Applied Genetics, 1998)

Net proton secretion as a parameter for nitrate uptake - M. A. Busch; M. Bttger (Protoplasma, 1997)

Inhibitory effects of oxidants on n-type K + channels in T lymphocytes and Xenopus oocytes - Ildikó Szabó; B. Nilius; Xinfeng Zhang; Andreas E. Busch; Erich Gulbins; Hartmut Suessbrich; Florian Lang (Pflügers Archiv - European Journal of Physiology, 1997)